2001
DOI: 10.1177/08959374010150010301
|View full text |Cite
|
Sign up to set email alerts
|

Pulp-capping with Recombinant Human Insulin- like Growth Factor I (rhIGF-I) in Rat Molars

Abstract: The aim of this study was to explore pulp healing and reparative dentinogenesis following pulp-capping by using recombinant human insulin-like growth factor I (rhIGF-I). Exposures were made through the mesial pulp horn in first upper molars in two-month-old Wistar rats. The pulp was covered with one dose of sterile 4% methylcellulose gel containing either 400 ng rhIGF-I or saline in contralateral controls. The exposure site was closed with sterile Teflon membrane, and the cavity was filled with IRM cement. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 22 publications
2
41
0
3
Order By: Relevance
“…recombinant insulin Like Growth Factor-i Lovschall H, et al, evaluated recombinant insulin like growth factor-I (rhIGF-I) in rat molars and concluded that dentin bridge formation was equal to dycal after 28 days [24].…”
Section: Growth Factorsmentioning
confidence: 99%
“…recombinant insulin Like Growth Factor-i Lovschall H, et al, evaluated recombinant insulin like growth factor-I (rhIGF-I) in rat molars and concluded that dentin bridge formation was equal to dycal after 28 days [24].…”
Section: Growth Factorsmentioning
confidence: 99%
“…98 Sert doku organik matriksinin önemli protein bileşenlerinden biri olan kemik sialoproteini ile gerçekleştirilen bir pulpa kaplaması deneyinde ise osteodentin ile birlikte görülen mineralize atübüler tamir dentini oluşumu gözlenmiştir. 99 In vitro olarak IGF-2, TGF-beta 1 ve BMP-7 kullanılarak yapılan pulpa kaplamasında reperatif dentinogenezisin indüklendiği görülmüştür.…”
Section: Biodentin(septodont Saint Maur Des Fossés France)unclassified
“…Currently many cytokines or bonding agents are enabled to calcification of the dental pulp, and clinical application has been operated as direct pulp capping agents [16][17][18] , But few calcification inducing substance for safety and derived from natural ingredients has been reported. Recently, Mineral Trioxide Aggregate (MTA) is excellent pulp capping or pulptomy 19,20) agents because of their high biocompatibility.…”
Section: Introductionmentioning
confidence: 99%